Observations of 5.9‐GHz Radio Propagation and 802.11p Network Performance at Road Junctions. Issue 5 (28th May 2019) - Clayton, C. J.; Stocker, A. J.; Alwane, S. K. A.; Hassan, D.
Abstract: The propagation of 5.9‐GHz radio signals and performance of an 802.11p network were measured at three road junctions each having a different density of buildings. The maximum range for which acceptable performance (defined as where the packet delivery ratio was greater than 90%) was dependent on the junction but lies in the range of 45–70 m. While reflections from transient vehicles were often found to have a small positive impact on network performance, this could not be relied upon to provide a reliable improvement in communications. The received signal strength was dependent on the junction type with the strong reflections from buildings located on the opposite side of a T‐junction leading to higher signal strength. Finally, an empirical relationship between the packet delivery ratio and the received signal strength has been established that will allow modelers to link signal strength to network performance for field conditions. Key Points: Observations of 802.11p performance at road junctions indicate that reliable communication can be expected at ranges of 45‐70 m In 70% of cases, the presence of vehicles marginally improves network performance An empirical relationship between received signal strength and network performance is presented